Effectiveness of Instruction Program on Pregnant Women’s Knowledge regarding Anemia at Primary Health Care Centers in Baquba City - Dawood, Qadessia; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2019)
Objective: to identify the effect of the Instruction program on the knowledge of pregnant women who suffering anemia.Methodology: A quasi-experimental design was carried out with the application of pre- post test for the study and the control group. Purposive sample, consists of (60) pregnant women diagnosed with anemia attending four health care centers in Baquba city.Result: The findings indicate that the level of hemoglobin is increasing post instructional program among women in the study group, in which (46.7%) of women are reveal a level of (8.1-9) g/dl that is less than normal pre instructional program and the level is increased to normal level post instructional program (10.1-11) g/dl in (53.3%) , and to (> 11 ) g/dl in (30%) of pregnant women. The results also present that the pregnant women in study group showing fair level of knowledge about anemia in pre-instructional program and their level increased to (100%) in post-instructional program. While the level of control group did not changed.Recommendation: Encourage the pregnant women to attained regular antenatal visits to detect early anemia and to upgrade maternal health status.`